Altered expression of small leucine-rich proteoglycans (Decorin, Biglycan and Lumican): Plausible diagnostic marker in urothelial carcinoma of bladder - Sandeep Appunni; Vivek Anand; Madhuram Khandelwal; Amlesh Seth; Sandeep Mathur; Alpana Sharma (Tumor Biology, 2017)
Small leucine-rich proteoglycans are components of extracellular matrix that regulates neoplastic transformation. Among small leucine rich proteoglycans, Decorin, Biglycan and Lumican are most commonly implicated markers, and their expression is well studied in various malignancies. In this novel study, we have collectively evaluated expression of these three molecules in urothelial carcinoma of bladder. Thirty patients of confirmed untreated bladder cancer, 30 healthy controls for blood and 30 controls for adjacent non-tumour tissue were enrolled. Blood was collected from all subjects and tumour/adjacent normal tissue was obtained from the patients. Circulatory levels were estimated by enzyme-linked immunosorbent assay, relative messenger RNA expression by quantitative polymerase chain reaction and protein expression by immunohistochemistry and western-blotting. Circulatory levels of Biglycan (p = 0.0038) and Lumican (p < 0.0001) were significantly elevated, and that of Decorin (p < 0.0001) was significantly reduced in patients as compared with controls. Protein expression by immunohistochemistry and western-blotting showed elevated expression of Lumican and Biglycan and lower expression of Decorin in urothelial carcinoma of bladder. Quantitative polymerase chain reaction for messenger RNA expression from tissue specimens revealed significantly higher expression of Biglycan (p = 0.0008) and Lumican (p = 0.01) and lower expression of Decorin (p < 0.0001) in urothelial carcinoma of bladder. Out of all molecules receiver operating characteristic curve showed that the 0.207 ng/ml cut-off of serum Lumican provided optimum sensitivity (90.0%) and specificity (90.0%). Significant alteration of matrix small leucine-rich proteoglycans in urothelial carcinoma of bladder was observed. Higher expression of Lumican in Bladder cancer patients with the cut-off value of highest optimum sensitivity and specificity shows its importance as a potential non-invasive marker for early detection of UBC following further validation in large patient cohort.